Morinda citrifolia como agente fotoprotetor - Serafini, Mairim Russo (2013)
Exposure to solar radiation, particularly its ultraviolet (UV), has a variety of harmful effects on human health. Some of these effects include sunburn cell formations, erythema, edema, melanoma, photoaging of the skin, and immune suppression. A plant that has been widely used in tropical folk medicine for a number of conditions is the Morinda citrifolia Linn. (Rubiaceae), commonly known as noni. The beneficial photoprotective effects of topical formulations based on extract from Morinda citrifolia leaves, have not yet been investigated. Thus, the present study aims to investigate the potential benefits of M. citrifolia topical application on the dorsal skin of mice, exposed to UVA-UVB light. Firstly, the absorption spectrum of the formulations extracts (10 and 15%) was evaluated by spectroscopy. The spectrum showed peaks at 200 nm and at 240 nm and absorption in the UVA and UVB regions. After 7 days of treatment and exposition to UVA-UVB light, the thickness, transepidermal water loss (TEWL), erythema and histological alterations were evaluated. The results from in vivo effectiveness showed that the thickness, TEWL values and erythema indexes were significantly decreased by treatment with formulations containing the extract. The histological measurements in hematoxilina eosin showed that in the non-irradiated group showed that the epidermis was represented by a thin, and continuous surface. No inflammatory infiltrate were found in the dermal tissues. Both irradiated and vehicle groups presented increased epidermal thickness associated to hyperorthokeratosis. The papillary dermis exhibited intense inflammatory infiltrate, mainly composed of lymphocytes, mild interstitial edema and prominent capillary and venular hyperemia. The treated groups presented remarkable reduction in the inflammatory content, as well as less expressive hyperemia. In the Sirius Red, the irradiated and vehicle groups, papillary dermis showed the presence of a gross, thick, parallel-arranged, collagen fibers. Both treated groups (10 and 15% formulations) presented similar features regarding the collagenization pattern, showing a mixture of yellowish type I and greenish type III collagen fibers. The interfibrillary spaces were more evident than in irradiated and vehicle groups. Such morphological appearances were very similar to that observed in non irradiated group. Areas treated with the formulation containing Morinda citrifolia extract (10% and 15%) have enhanced protection against UV radiation. Finally, the extract was evaluated on murine malignant melanoma (cell line B16F10) in order to examine their cytotoxic effects on malignany cells. The extract at concentrations of 0.05 to 12.8 mg/mL did not show any cytotoxic effects in the B16F10 cell line. These can suggest that the extract showed no potential anti cancer in melanoma cells, and the extract have only photoprotection effects. In conclusion, the results showed that the formulations containing the extract protected the skin against UV-induced damage.